2020
DOI: 10.1007/jhep10(2020)144
|View full text |Cite
|
Sign up to set email alerts
|

Complex Langevin calculations in QCD at finite density

Abstract: We demonstrate that the complex Langevin method (CLM) enables calculations in QCD at finite density in a parameter regime in which conventional methods, such as the density of states method and the Taylor expansion method, are not applicable due to the severe sign problem. Here we use the plaquette gauge action with β = 5.7 and four-flavor staggered fermions with degenerate quark mass ma = 0.01 and nonzero quark chemical potential μ. We confirm that a sufficient condition for correct convergence is satisfied f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
(69 reference statements)
2
15
0
Order By: Relevance
“…In Refs. [ 103 , 106 , 107 ], the average quark number is studied on lattices with sizes and . The authors found a plateau for as a function of the chemical potential.…”
Section: Low Finite Densitymentioning
confidence: 99%
“…In Refs. [ 103 , 106 , 107 ], the average quark number is studied on lattices with sizes and . The authors found a plateau for as a function of the chemical potential.…”
Section: Low Finite Densitymentioning
confidence: 99%
“…In order to confirm this phenomenon, we clearly need to increase the lattice size. We have already started simulations on a 8 3 × 16 lattice [36] and found that the CLM actually gives correct results even in the region of relatively large chemical potential without the deformation technique. Preliminary results for the baryon number density and the chiral condensate show a rapid change twice as we increase the chemical potential, which may be interpreted as the phase transitions to the nuclear matter and to the quark matter.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In Ref. [36][37][38] Complex Langevin simulations in small boxes with sizes of 8 3 × 16 and 16 3 × 8 with four flavors and a lattice spacing of 𝑎 −1 ≈ 4.7 GeV were performed. For the dependence of the quark number on the chemcial potential a plateau was observed that the authors relate to the Fermi surface and color superconductivity.…”
Section: Complex Langevinmentioning
confidence: 99%